Flux of C, N and P return to the soil in two species of remainder trees in a seasonal tropical pasture - Galicia, Leopoldo; García-Oliva, Felipe; Murillo, Ramón; Oliva, Magdalena (Instituto de Ecología, A.C., 2002)
We investigated the differences between two trees species in total C, N and P concentrations in live leaves, literfall, and surface litter. The work was conducted on individuals remnant in pastures, in a tropical deciduous forest ecosystem on the coast of Jalisco, Mexico. The use of nutrients differed between the two species: Cordia elaeagnoides had higher P concentration in live leaves, litterfall and surface litter than Caesalpinia eriostachys, but the latter species had a higher P use-efficiency. In contrast, the amount of nutrients fluxed through litterfall varied among years, suggesting that the productivity of specific year determined the amount of nutrients returned to the soil. However, the magnitude of this effect can be depleted by the short residence time of organic matter and nutrients of surface litter associated to both species.